Fotoreportaje que evidencia la riqueza cultural andina del Pawkar Raymi en Peguche Imbabura. - Guerra Serrano, Jasón Andrés (2017)
This work was done in order to show the entire Andean cultural area that has the popular festival of Pawkar Raymi; this festival consists of different symbolic manifestations that bring out the richness of the traditions and customs of the Andean region. The Pawkar Raymi is a popular Andean festival that is celebrated to give thanks to the Pachamama for the new crops received and represents the initiation of the year of festivities as the Inca calendar points out. The preparations for the festival begin in January of each year and culminate in March, full of traditions; this festivity has different meanings in indigenous life, where an ancestral connection with nature is created. The Andean cultural richness is affected by many areas, one of the main ones is the colonization, since the current society adopts different cultures reflecting how a process of conquest lived, what one seeks to transmit with this work is to demonstrate all this intercultural process that carries out a spiritual and important celebration for the indigenous community of Peguche. Another important aspect is to show through a photo essay, as the ancestral knowledge of the Communities act as a philosophy of life, they seek to socialize these knowledge that reflect how a community is formed based on the spiritual and ceremonial, the Andean world view has different factors that represent a way of living in harmony with the environment and allows the representation of culture and ideology.